Checkpoint Charley : 4. Berlin-Biennale für Zeitgenössische Kunst. - Cattelan, Maurizio; Gioni, Massimiliano; Subotnick, Ali; Berlin Biennale für Zeitgenössische Kunst 2006 Berlin (Berlin : KW Institute for Contemporary Art, 2006)
Brisley, Stuart ; Lorenz, Susanne ; Lovsin, Polonca ; Ferrarese, Valentina ; Fröhlich, Fred ; Lück, René ; Low, Antonia ; Penalva, Joao ; Sullivan, Catherine ; De Dominicis, Gino ; et al.
This publication brings together images produced by more than 700 artists encountered in studios, found in catalogues and recommended by friends and colleagues
kunstcatalogus